1994
DOI: 10.1093/jn/124.5.607
|View full text |Cite
|
Sign up to set email alerts
|

The Chemoprevention of Cancer by Mevalonate-Derived Constituents of Fruits and Vegetables

Abstract: Anutritive isoprenoid constituents of fruits, vegetables, cereal grains and essential oils exhibit a spectrum of anticarcinogenic activities. The induction of hepatic Phase II detoxifying activities by dietary isoprenoids appears to underlie their blocking action. The second anticarcinogenic action of the dietary isoprenoids, suppression of the growth of chemically initiated and transplanted tumors is, we suggest, secondary to the inhibition of mevalonate pathway activities. Mevinolin, a competitive inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
2
9

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(70 citation statements)
references
References 53 publications
1
58
2
9
Order By: Relevance
“…These are the two basic unities from which the monoterpenes are formed. This is the same pathway that makes cholesterol in humans and animals (Elson & Yu, 1994). Earlier on, cancer researchers realized that some aspects of cholesterol metabolism were involved in the tumor growth.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…These are the two basic unities from which the monoterpenes are formed. This is the same pathway that makes cholesterol in humans and animals (Elson & Yu, 1994). Earlier on, cancer researchers realized that some aspects of cholesterol metabolism were involved in the tumor growth.…”
Section: Introductionmentioning
confidence: 97%
“…Earlier on, cancer researchers realized that some aspects of cholesterol metabolism were involved in the tumor growth. They then discovered that plant monoterpenes interfered with animal cholesterol synthesis, thereby reducing cholesterol levels and reducing tumor formation in animals (Elson & Yu, 1994). Monoterpenes also increase the levels of liver enzymes involved in the detoxification of carcinogens; an effect that decreases the possibility of carcinogens causing the cellular damage.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Failing to demonstrate an inverse relationship between cancer incidence and consumption of the vitamins prominent in these plant products, investigators have turned attention to the many classes of nutrient phytochemical constituents also present in these foods. 5 Specific isoprenoids, culled from a group of some 22,000 products of secondary plant metabolic pathways sharing a common precursor, mevalonic acid, 6 have demonstrated anticarcinogenic and chemoprotective activities. One phytochemical compound, b-ionone, an end ring analog of b-carotenoid, represents a subclass of cyclic isoprenoids.…”
mentioning
confidence: 99%
“…Tocotrienols have three double bonds, and an unsaturated side chain that renders them greater fluidity and makes them easily accessible to cells with saturated fatty acid layers to be incorporated into cell membranes (Das et al 2008b). Evidence suggests that the level of phytyl chain saturation and/or chroman ring methylation is critical in determining the differential biopotencies demonstrated by individual vitamin E isoforms (Crowell et al 1991;Elson and Yu 1994;McIntyre et al 2000;Sen et al 2000). A comparative study between tocotrienols and tocopherols showed that tocotrienols are significantly more potent than tocopherols in most biological actions and display a consistent relationship in most instances corresponding to d-ocotrienol C c-tocotrienol [ a-tocotrienol [ d-tocopherol [ c-, and a-tocopherol (Shukla and Gupta 2005;Sporn and Suh 2002).…”
Section: Structure-activity Relationship Of Tocotrienolsmentioning
confidence: 99%